Investigation on unstable flow characteristics and energy dissipation in Pelton turbine - Wenrui Fan; Longgang Sun; Pengcheng Guo (Engineering Applications of Computational Fluid Mechanics)
The internal flow scale of a Pelton turbine is variable, and the interaction between the jet and the bucket has strong transient characteristics, resulting in an incomplete understanding of its internal vortex structure evolution and energy dissipation mechanisms. In order to reveal the influence of vortices on the flow regime and energy dissipation mechanisms in the turbine, this paper establishes the correlation between the unsteady flow characteristics and energy dissipation inside the Pelton turbine based on the energy balance equation and quantifies the energy losses inside the turbine. The results indicate that vortex structures present a non-uniform distribution inside the jet, which disrupts the uniformity of the jet velocity distribution, resulting in an uneven distribution of high-vorticity zones on the bucket surfaces and intensifying flow interference among the buckets. The strong shear flow caused by the downstream flow detachment of the needle guide, the turbulent boundary layer on the jet surface, and the wake effect downstream of the needle tip are the main reasons for the dissipation of fluid kinetic energy. The distribution range of energy loss on the rotating bucket closely corresponds to the position of the high-vorticity zone. Energy dissipation inside the turbine is primarily in the form of turbulent kinetic energy, and the injectors and runner are the primary energy dissipation components. Moreover, inside the injectors, each form of energy loss remains relatively constant, whereas inside the runner, its rotation induces fluctuating energy losses attributed to Reynolds stress work. The results contribute to an enhanced understanding of the energy dissipation characteristics and complex flow mechanisms within the turbine, providing reference for the optimisation and efficient operation of the multi-nozzle Pelton turbine.